THE RELATIONSHIP BETWEEN DEMOGRAPHIC ATTRIBUTES, DIET KNOWLEDGE VERSUS RISK FACTORS OF POLYCYSTIC OVARIAN SYNDROME AMONG NURSING COLLEGE STUDENTS - Kadhim A, Thikra Abdul (PT. Antis International Publisher, 2025)
Objective: This study examines the relationships between demographic attributes, dietary knowledge, and PCOS risk factors among nursing college students to identify determinants that influence syndrome awareness and symptom recognition. Method: A cross-sectional descriptive study was conducted among 120 female nursing students using a structured questionnaire covering demographic characteristics, dietary knowledge related to PCOS, and self-reported risk factors. Results: Significant correlations were identified between age groups and specific risk factors, with younger students showing a higher prevalence of certain symptoms. Dietary knowledge levels varied considerably, with 47.5% demonstrating good understanding, while 50% showed moderate awareness. Strong associations emerged between family history, lifestyle factors, and symptom presentation. Novelty: Demographic characteristics and nutritional literacy significantly influence PCOS risk factor recognition among nursing students, highlighting the need for targeted educational interventions in healthcare curricula.